Preschool Wheezing and Progress to Childhood Asthma - Boriçi, Sonila (International Journal of Child Health and Nutrition, 2025)
Aim: This narrative review aims to identify key elements that facilitate the transition from recurrent episodes of wheezing to chronic inflammatory airway disease. Methods: The article presents the results of numerous studies that identify the influence of genetic and environmental factors on the development of asthma in children. Whole-genome data analysis revealed novel genetic loci associated with various asthma phenotypes. Additionally, the study underscored the significance of environmental factors, such as air pollution and microbial colonization, in the disease’s onset. Results: The results provided a foundation for developing new prevention and treatment strategies for childhood asthma, emphasizing a personalized approach that considers each patient’s unique genetic and environmental profile. The main findings indicate that up to 50% of children under 6 years old experience wheezing episodes, but only 30% of these children develop asthma. Data analysis demonstrated that both genetic and environmental factors significantly influence asthma development in children with preschool wheezing. Genetic research has identified several genes associated with early-onset asthma, including CDHR3, IL33, and genes at the 17q12-21 locus. Surrounding conditions such as viral infections, allergens, tobacco smoke, and the microbiome also play a substantial role in asthma development. Conclusions: Understanding the relationship between hereditary and environmental influences in the advancement from preschool wheeze to asthma is crucial for developing effective prophylactic and treatment strategies. The study of factors influencing the development of asthma in children is important for understanding the mechanisms of disease formation and developing effective methods of prevention and treatment. Special attention is paid to the interaction of genetic and external factors influencing the early stages of pathogenesis.